Masharipov SH.M1., Kenjayeva Z.S2., Ernazarova3 Z.X., Rahmatullayev S.A4., Fattoyev5 F.F. - Masharipov SH.M., Kenjayeva Z.S., Ernazarova Z.X., Rahmatullayev S.A., Fattoyev F.F. (International Journal of Advanced Science and Technology, 2020)
The article discusses the peculiarities of the assessment of uncertainty of the indicators of food products. In accordance with ISO/IEC 17025-2017, it is important that analysts know that each analytical result has its own uncertainty value and are able to assess this uncertainty. Different procedures can be used to estimate measurement uncertainty. To achieve GUM (Guide to the expression of uncertainty in measurement) goals, food laboratories must apply precision controls, use methods tested by multiple laboratories or properly validated, if any, for analysis, and assess the suitability of the methods before applying them for analysis in accordance with established practice. Thus, food laboratories have sufficient data that can be used to estimate measurement uncertainty. Measurement uncertainty typically contains many components. Some of these components can be estimated from the statistical distribution of the results of the series of measurements and characterized by experimentally obtained standard deviations. Other components, which can also be characterized using standard deviations, are evaluated based on an assumed probability distribution based on experimental data or other information. The main sources of uncertainty in the measurement of food indicators are shown.